Spectrophotometric Determination of Etodolac - YE, YANQING; YINKE, LI; YUN, HUANG (Asian Journal of Chemistry, 2010)
A simple, sensitive and reproducible spectrophotometric method for the determination of etodolac was described. This method based on the oxidation of the studied drugs by Fe3+ in the presence of o-phenanthroline (o-phen) medium. The formation of tris-complex upon reactions with Fe3+-o-phen in an acetate buffer solution of the optimum pH-values was demonstrated at 510 nm with o-phen. The concentration ranges are from 0.5-20 μg/mL for this method. For more accurate analysis, Ringbom optimum concentration ranges were calculated. The molar absorptivity, Sandell sensitivity, detection and quantification limits were also calculated. The developed method was successfully applied to the determination of etodolac in bulk and pharmaceutical formulations without any interference from common excipients. The relative standard deviations were ≤ 0.76 % with recoveries 99-101 %.